Nanomaterial Fabrication through the Modification of Sol–Gel Derived Coatings - Wai Kian Tan; Hiroyuki Muto; Go Kawamura; Zainovia Lockman; Atsunori Matsuda (Nanomaterials, 2021)
In materials processing, the sol–gel method is one of the techniques that has enabled large-scale production at low cost in the past few decades. The versatility of the method has been proven as the fabrication of various materials ranging from metallic, inorganic, organic, and hybrid has been reported. In this review, a brief introduction of the sol–gel technique is provided and followed by a discussion of the significance of this method for materials processing and development leading to the creation of novel materials through sol–gel derived coatings. The controlled modification of sol–gel derived coatings and their respective applications are also described. Finally, current development and the outlook of the sol–gel method for the design and fabrication of nanomaterials in various fields are described. The emphasis is on the significant potential of the sol–gel method for the development of new, emerging technologies.